Annual Review of Gerontology and Geriatrics 24, 2004 : Intergenerational Relations Across Time and Place. - Silverstein, Merril (Springer Pub. Co., 2004)
This volume examines the importance of time and place, as applied to aging families. In the first section, chapters focus on the temporal dimension of intergenerational relations using frameworks from human development, sociology, social history, and social psychology. The second section focuses on the social ecology of intergenerational relations in terms of the national contexts within which families are embedded. The contributors demonstrate how the social, cultural, historical, and institutional forces that orient older and younger family members toward each other in both structured and ad.